2001
DOI: 10.1038/sj.ijo.0801528
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an increased free fatty acid concentration on thermogenesis and substrate oxidation in obese and lean men

Abstract: OBJECTIVE:To examine whether a certain increase in plasma free fatty acid (FFA) concentration leads to similar increases in lipid oxidation and energy expenditure in obese and lean men. DESIGN: The study protocol consisted of a 30 min baseline period after which subjects received an i.v. bolus of 1000 IE heparin. Then consecutive infusions of 4.9, 9.8 and 19.6 mlakg fat-free mass (FFM) Á min of a lipid heparin mixture were started, each infusion for 30 min. SUBJECTS: Eleven obese and 13 lean men with a mean bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
(22 reference statements)
4
14
1
2
Order By: Relevance
“…This suggests that lipid oxidation and thermogenesis are impaired in the obese independently from NEFA availability. Our ␤ 1 -adrenoceptor study and the study using lipid heparin infusion (35) show that similar increases in thermogenesis and lipid oxidation occur in obese and lean men for a certain increase in plasma NEFA concentration, and therefore do not support these findings. The reduced increase in plasma NEFA and glycerol concentrations and the consequent reduced increases in lipid oxidation and thermogenesis during ␤ 2 -adrenergic stimulation might be explained not only by a defect in the ␤ 2 -adrenoceptor or the pathways it mediates, as stated above, but also by the slightly higher increase in insulin concentration in the obese, because insulin inhibits lipolysis.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This suggests that lipid oxidation and thermogenesis are impaired in the obese independently from NEFA availability. Our ␤ 1 -adrenoceptor study and the study using lipid heparin infusion (35) show that similar increases in thermogenesis and lipid oxidation occur in obese and lean men for a certain increase in plasma NEFA concentration, and therefore do not support these findings. The reduced increase in plasma NEFA and glycerol concentrations and the consequent reduced increases in lipid oxidation and thermogenesis during ␤ 2 -adrenergic stimulation might be explained not only by a defect in the ␤ 2 -adrenoceptor or the pathways it mediates, as stated above, but also by the slightly higher increase in insulin concentration in the obese, because insulin inhibits lipolysis.…”
Section: Discussioncontrasting
confidence: 53%
“…5, there was a clear relationship between the increases in plasma NEFA concentration and the increases in energy expenditure and lipid oxidation during ␤ 1 -and ␤ 2 -adrenergic stimulation. Furthermore, we recently reported that for a certain increase in plasma NEFA concentration produced by lipid heparin infusion, similar increases in thermogenesis and lipid oxidation are found in obese and lean men (35). These data suggest that not only ␤ 2 -adrenergic stimulation but also NEFA availability might be related to the blunted responses in thermogenesis and lipid oxidation.…”
Section: Discussionmentioning
confidence: 72%
“…Higher plasma FFA concentration may increase lipid oxidation and in turn the reliance on glucose as a source of energy (19). Additionally, plasma FFA may reduce insulin-stimulated glucose uptake (20).…”
Section: Discussionmentioning
confidence: 99%
“…(11) and as adipocytes contain more lipids in obesity, the exosomes they secrete may be enriched in fatty acids, known positive regulators of FAO (25).…”
Section: Discussionmentioning
confidence: 99%